Effect of Maxillary Osteotomy on Speech in Cleft Lip and Palate: Instrumental Outcomes of Velopharyngeal Function. - Pereira, Valerie J.; Tuomainen, Jyrki; Hay, Norman; Mars, Michael; Suchak, Archna; Sell, Debbie A. (Cleft Palate Craniofacial Journal, 2020)
Objective: To investigate the effect of maxillary osteotomy on velopharyngeal function in cleft lip and palate (CLP) using instrumental measures. Design: A prospective study. Participants: A consecutive series of 20 patients with CLP undergoing maxillary osteotomy by a single surgeon were seen at 0 to 3 months presurgery (T1), 3 months (T2), and 12 months (T3) post-surgery. Interventions: Nasalance was measured on the Nasometer II 6400. For videofluoroscopy and nasendoscopy data, visual perceptual ratings, for example, palatal lift angle (PLAn), and quantitative ratiometric measurements, for example, closure ratio (CRa), were made using a validated methodology and computer software. Reliability studies were undertaken for all instrumental measures. Main Outcome Measures: Repeated measures analysis of variance (with time at 3 levels) for nasalance and each velar parameter. Planned comparisons across pairs of time points (T1-T2, T1-T3, and T2-T3) including effect sizes. Results: A significant difference over time was found for nasalance (P =.001) and planned comparisons across pairs of time points were significant between T1 and T2 (P =.008), T1 and T3 (P =.002), but not between T2 and T3 (P =.459) providing evidence that maxillary osteotomy can impact on nasalance adversely and that the changes seen are permanent and stable. There were also significant differences over time for PLAn (P =.012) and CRa (P = −.059) and planned comparisons for both velar parameters reflected similar findings to those of nasalance. Conclusions: Maxillary osteotomy can adversely affect velopharyngeal function in patients with CLP. The study provides evidence for a much earlier post-surgery review even as early as 3 months after surgery.